2013
DOI: 10.1158/0008-5472.can-12-4051
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Risk Associated with Hormone Use Varies by Expression of Estrogen Receptor-β

Abstract: The risk of colorectal cancer is reduced among users of oral contraceptives or menopausal hormone therapy, but associations with reproductive characteristics that are markers of a woman's endogenous hormone milieu have not been consistently observed. To help understand possible mechanisms through which exogenous and endogenous hormonal exposures are involved in colorectal cancer, we assessed the risk of these malignancies according to tumor expression of estrogen receptor-b (ESR2). In a population-based study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
(47 reference statements)
1
34
0
1
Order By: Relevance
“…The summary RRs for the longest versus shortest were 0.85 (95 % CI 0.74-0.97), almost identical to the results of the primary analyses. Meanwhile, exclusion of two studies [27,38] in which RRs and 95 % CI were not reported but calculated from raw data or five studies [24,38,39,42] not adjusted for any confounders or two studies [22,23] reporting the risk estimates with CRC mortality, the results were similar to the original analysis (data not shown).…”
Section: Sensitivity Analysesmentioning
confidence: 57%
See 3 more Smart Citations
“…The summary RRs for the longest versus shortest were 0.85 (95 % CI 0.74-0.97), almost identical to the results of the primary analyses. Meanwhile, exclusion of two studies [27,38] in which RRs and 95 % CI were not reported but calculated from raw data or five studies [24,38,39,42] not adjusted for any confounders or two studies [22,23] reporting the risk estimates with CRC mortality, the results were similar to the original analysis (data not shown).…”
Section: Sensitivity Analysesmentioning
confidence: 57%
“…We extracted the RRs that reflected the greatest degree of control for potential confounders for use in the main analyses. If no estimate was presented in a given study, we calculated it and its 95 % CI according to the raw data presented in the article [27,38]. Similar to our previous studies [44,45], we did not assess study quality using a quality score, but investigated whether specific study characteristics, such as study design and adjustment for confounders, which are indicators of study quality, influenced the results in subgroup analyses.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of exogenous hormones is associated with a decreased risk for estrogen receptor-b-positive (ERb-positive), but not estrogen receptor-b-negative (ERb-negative) colorectal cancer (Rudolph et al, 2013). Although ERa and ERb are the two known subtypes through which estrogens exert their effects on various tissues, ERb is the predominant estrogen receptor subtype in the human colon and decreased levels of ERb are associated with colonic tumorigenesis (Campbell-Thompson et al, 2001;Pampaloni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%